EFFECTIVENES OF THE ROLE OF BOARD OF COMMISSIONER IN PREVENTING CORPORATE SCANDAL: CASE STUDY OF PT MERPATI NUSANTARA AIRLINES - Erbiana, Nyi Mas Gianti Bingah (DERECHTSSTAAT, 2018)
Corporate scandal resulted from bad consideration and weak analysis to create management decision in running companyâs business. This paper discusses the supervisory role and function of supervisory board which is begun with the establishment of corporate supervisory function system from two corporate supervisory system in the world: Two-Tier Baord and One-Tier Board. In addition, this paper also explains connection between such supervisory function with the corporate scandal of PT Merpati Nusantara Airlines. Moreover, this paper examines related matters related to significant distinctions between response towards the corporate scandal based on the corporate management supervision. In conclusion, this paper addresses what can we learn from the corporate scandal of PT Merpati Nusantara Airlines and also whether supervision model by board of commissioners are still relevant to control the performance of the company.